2020
DOI: 10.1515/erj-2019-0308
|View full text |Cite
|
Sign up to set email alerts
|

Does Entrepreneurship Matter for Inclusive Growth? The Role of Social Progress Orientation

Abstract: Building upon institutional economics, we examine how social progress orientation (SPO) affects inclusive growth through innovative and opportunity entrepreneurship. Hypotheses about civic activism, voluntary spirit, and the inclusion of minorities as proxies of SPO that affect entrepreneurship directly and inclusive growth indirectly have been suggested. Using unbalanced panel data of 132 observations (63 countries) and the three-stage least-squares method (3SLS), we provide empirical evidence that these thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 183 publications
0
11
0
1
Order By: Relevance
“…Important efforts have been made regarding analyses on social outcomes such as poverty reduction [33], inequality [34], inclusive growth [2], and gender equality [35]. Although it is not as abundant as compared to the analysis of traditional economic growth, this literature confirms that entrepreneurs have a social sense, implying that their decisions transcend materialism and the money-making mindset.…”
Section: Social Sustainable and Economic Outcomes Of Entrepreneurshipmentioning
confidence: 97%
See 2 more Smart Citations
“…Important efforts have been made regarding analyses on social outcomes such as poverty reduction [33], inequality [34], inclusive growth [2], and gender equality [35]. Although it is not as abundant as compared to the analysis of traditional economic growth, this literature confirms that entrepreneurs have a social sense, implying that their decisions transcend materialism and the money-making mindset.…”
Section: Social Sustainable and Economic Outcomes Of Entrepreneurshipmentioning
confidence: 97%
“…Extant research has shown that if societies are oriented toward progress, then these societies provide a suitable environment for entrepreneurs, who in exchange, create social benefits [2,31]. Indeed, econometrically speaking, the existing loop (i.e., endogeneity) between entrepreneurship and development is overcome thanks to the presence of institutions that positively affect entrepreneurial activity in one way or another.…”
Section: Social Sustainable and Economic Outcomes Of Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Demokrasi deliberatif mengakselerasi pertumbuhan ekonomi inklusif, kualitas pengambilan keputusan, akuntabilitas, ikatan sosial, kepercayaan, dan pengetahuan warga (Aparicio et al, 2021). Deliberasi krusial bagi penyusunan dan implementasi kebijakan publik yang strategis.…”
Section: Demokrasi Deliberatifunclassified
“…We are aware that a lack of data sources poses a challenge to overcome, particularly when attempting to conduct cross-country comparisons, due to the limited number of indicators and the differences in measurements across countries [107]. Further efforts are needed to create homogenous information concerning green entrepreneurship, as well as its antecedents and those consequences beyond economic terms [108]. Future research should improve the quality and scope of the indicators, for both dependent, as well as independent variables, which may increase reliability and the ability to analyze causal relationships in a cross-sectional setting [18].…”
Section: Limitations and Future Researchmentioning
confidence: 99%